1995
DOI: 10.1074/jbc.270.37.21950
|View full text |Cite
|
Sign up to set email alerts
|

Contraction Accelerates Myosin Heavy Chain Synthesis Rates in Adult Cardiocytes by an Increase in the Rate of Translational Initiation

Abstract: The purpose of this study was to determine the mechanism by which contraction acutely accelerates the synthesis rate of the contractile protein myosin heavy chain (MHC). Laminin-adherent adult feline cardiocytes were maintained in a serum-free medium and induced to contract at 1 Hz via electrical field stimulation. Electrical stimulation of contraction accelerated rates of MHC synthesis 28%, p < 0.05 by 4 h as determined by incorporation of [ 3 H]phenylalanine into MHC. MHC mRNA expression as measured by RNase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 39 publications
4
32
0
Order By: Relevance
“…5, which is published as supporting information on the PNAS web site). Comparable levels of mRNA in all groups are consistent with translational regulation (15). With time in culture, the ratio of ␣-MHC (mature) and ␤-MHC (neonatal) isoforms decreased in nonstimulated and increased in stimulated constructs, suggesting that the maturation of cardiomyocytes depended both on culture duration and electrical stimulation.…”
Section: Resultssupporting
confidence: 49%
“…5, which is published as supporting information on the PNAS web site). Comparable levels of mRNA in all groups are consistent with translational regulation (15). With time in culture, the ratio of ␣-MHC (mature) and ␤-MHC (neonatal) isoforms decreased in nonstimulated and increased in stimulated constructs, suggesting that the maturation of cardiomyocytes depended both on culture duration and electrical stimulation.…”
Section: Resultssupporting
confidence: 49%
“…We indeed found that the presence of ΨCx43 transcript in these cell lines resulted in a shift of Cx43 mRNA levels from the polysome fractions toward the monosomes in Hs578T cells and to an overall decrease in Cx43 mRNA in the polysomes of MDA 231 cells. These findings suggest that ΨCx43 inhibits both the translational initiation and efficiency of Cx43 mRNA (37,38).…”
Section: Molecular Cancer Therapeuticsmentioning
confidence: 78%
“…After a 15 min incubation on ice, the homogenate was centrifuged at 12,000×g to produce a post-mitochondrial supernatant. The supernatant was layered onto a 15-50% linear sucrose gradient in a buffer containing 200 mM Tris-HCl (pH 7.5), 2.5 M KCl, and 100 mM MgCl 2 , and centrifuged at 100,000×g for 100 min at 4° C. A density gradient fractionator (Teledyne Isco, Inc.) was used to isolate monosome fractions (messenger ribonucleoprotein particles and free ribosomes) and polysome fractions [15]. The RNA in each fraction was extracted using Trizol® reagent.…”
Section: Isolation Of Polysome Fractions From Murine Myocardiummentioning
confidence: 99%